Gender and timebound commandments in Judaism - Alexander, Elizabeth Shanks, 1967- (Cambridge ; New York : Cambridge University Press, 2013)
"The rule that exempts women from rituals that need to be performed at specific times (so-called timebound, positive commandments) has served for centuries to stabilize Jewish gender. It has provided a rationale for women's centrality at home and their absence from the synagogue. Departing from dominant popular and scholarly views, Elizabeth Shanks Alexander argues that the rule was not conceived to structure women's religious lives, but rather became a tool for social engineering only after it underwent shifts in meaning during its transmission. Alexander narrates the rule's complicated history, establishing the purposes for which it was initially formulated and the shifts in interpretation that led to its being perceived as a key marker of Jewish gender. At the end of her study, Alexander points to women's exemption from particular rituals (Shema, tefillin, and Torah study), which, she argues, are better places to look for insight into rabbinic gender"--
Part I. Gender and the Tannaitic Rule: 1. The rule and social reality: conceiving the category, formulating the rule; 2. Between man and woman: lists of male-female difference -- Part II. Talmudic Interpretation and the Potential for Gender: 3. How tefillin became a positive commandment not occasioned by time; 4. Shifting orthodoxies; 5. From description to prescription -- Part III. Gender in Women's Ritual Exemptions: 6. Women's exemption from Shema and tefillin; 7. Torah study as ritual; 8. The fringes debate: a conclusion of sorts -- Epilogue.
Includes bibliographical references (p. 251-262) and indexes.
Description based on print version record.
Keywords: Women in Judaism; Sex role -- Religious aspects -- Judaism; Feminism -- Religious aspects -- Judaism; Jewish women -- Religious life; RELIGION / Judaism / Rituals & Practice; Electronic books